Traumatic dental injuries in the Eastern Region of Saudi Arabia: Factors influencing teachers' management practices. Issue 1 (24th September 2020) - Gaffar, Balgis; AlHumaid, Jehan; Ashraf Nazir, Muhammad; Alonaizan, Faisal
Abstract: Background/Aims: Traumatic dental injuries (TDIs) in children frequently occur in schools where teachers can play an important role in their management. Therefore, the aim of this study was to assess schoolteachers' knowledge and the factors that determine their management of TDIs. Materials and methods: This cross‐sectional study was conducted in the Eastern Province of Saudi Arabia from January to June 2018. Data were collected through an online pre‐tested questionnaire. The questionnaire collected demographic data and included questions that assessed participants' knowledge and management practices for TDI. Chi‐square test and multivariate logistic regression analysis were performed. Results: A total of 443 teachers were included in the study, and 72.5% of the participants were females. The prevalence of TDIs was 49% yet only 7.2% of the participants reported managing dental trauma. Fights (22.8%) and falls (21.7%) were the most common causes of dental injuries. Mean TDI knowledge score was 2.75 ± 2.05, but only 47.2% were willing to receive training about TDI management. Regarding supportive environments, 75.8% of teachers reported having safety playgrounds, however 10.6% reported having a nurse in schools. After controlling for other variables, male respondents were 3.85 times more likely to manage TDIs than female respondents ( P = .001). Similarly, previous knowledge of dental trauma management (OR = 4.32, P < .001) and having less than 50 students in class (OR = 2.61, P = .021) were significantly associated with TDI management. Conclusion: The teachers demonstrated inadequate knowledge about TDIs which were highly prevalent in primary schools. Male gender, having knowledge of TDI management and teaching less students were associated with increased likelihood of TDI management. There is a crucial need for the reinforcement of policies that support school safety and a supportive environment.